PENGGAMBARAN KARAKTER CHANG’E DALAM FILM “OVER THE MOON” - Natasya Andriana; Selvia Selvia (Universitas Sebelas Maret, 2023)
Myths and legends have been told from generation to generation by being spoken from thousands of years ago. Myth in Chinese language is Shen hua (神话), shen means god, spirit and holy; hua is a saying, a fairy tale, an oral story. In the movie “Over the Moon”, there are characters in Chang'e’s legend story, such as Hou Yi, even the Jade rabbit appears in the movie. The portrayal of Chang'e's character in the film has undergone several changes and “Alih Wahana” by filmmaker's. Therefore, researchers are interested in analyzing the depiction of Chang'e in the film